Influence of fertilizers and soil treatment on the balance of nutrients in the crop rotation - Лукашук, В. П. (Scientific Progress & Innovations, 2016)
The results of the impact study of organic, mineral and organic-mineral systems of fertilizers compared with control without systems and different tillage systems on balance of nutrients while growing of crops in rotation. We found that use only organic fertilizer system, as well as the mineral is not enough to achieve an entailing no deficit balance of nitrogen, phosphorus and potassium while the vast majority of crops’ growing. Application of organic-mineral system of fertilization on meadow drained soils can achieve an entailing no deficit balance of nitrogen, phosphorus, and potassium for the vast majority of growing crops. Regarding the impact of tillage systems, the studies showed that it had little impact on the balance of nitrogen, phosphorus, and potassium in rotation.